PELAKSANAAN PROMOSI ANGGOTA ASITA JAWA BARAT DALAM MENGHADAPI TREN ONLINE TRAVEL AGENT - Dwiesty Dyah Utami; Vany Octaviany (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
In recent years, the emergence of the online electronics market has dramatically changed the travel industry (Shapiro & Shi, 2008). In addition, the emergence of information and communication technology encourages tourism to online channels. Suppliers and middlemen are now struggling in the fierce competition to sell their services through e-commerce (Vilarinho, 2014). This requires ASITA and its members to face the trend of online travel agents, one of them uses promotions related to the development of digital trends. This study uses quantitative research methods, with descriptive statistical analysis techniques and Likert Scale analysis tools, and based on Lupiyoadi & Hamdani's theory of service promotion mix. Data Collection Techniques with Questionnaires, Interviews, Library Studies, Observation. Population in this research is 193 travel agents and all consumers come to the travel agent member ASITA West Java in Bandung on 17 - 28 October 2016. The sample of research is 270 consumers and 18 travel agent members ASITA. The results of the research analysis showed that individual consumers are very interested in sales promotion, public relations, and word of mouth promotion. While corporate consumers, interested in individual sales and direct marketing. So ASITA members can focus on optimizing the promotion mix that consumers very interested in and ASITA can create a national portal that contains comparative travel agent member ASITA West Java.